2020
DOI: 10.18549/pharmpract.2020.3.2017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of potentially inappropriate prescriptions in primary care and correlates with mild cognitive impairment

Abstract: Background: Potentially inappropriate prescribing is clearly associated with adverse health consequences among older people. Nevertheless, scarce evidence exists regarding the prevalence of potentially inappropriate prescriptions (PIP) in Albania, a Western Balkans country. Objective: The aim of this study was to assess the prevalence of PIP among older Albanian patients in primary care and to determine the associated sociodemographic and medical factors, including the presence of mild cognitive impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Table 1 presents the main characteristics of the 33 studies included in this systematic review. The majority of studies were conducted in Europe ( n = 13) [ 20 , 46 , 49 , 53 , 54 , 56 , 61 , 64 , 69 , 70 , 74 76 ], ten were conducted in North America [ 47 , 48 , 51 , 52 , 57 , 58 , 60 , 65 , 67 , 72 ], four in South America [ 59 , 62 , 63 , 68 ], three in Asia [ 50 , 66 , 71 ], two in Australia [ 22 , 55 ] and one in Africa [ 73 ]. Most studies ( n = 23) used a cross-sectional design.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 presents the main characteristics of the 33 studies included in this systematic review. The majority of studies were conducted in Europe ( n = 13) [ 20 , 46 , 49 , 53 , 54 , 56 , 61 , 64 , 69 , 70 , 74 76 ], ten were conducted in North America [ 47 , 48 , 51 , 52 , 57 , 58 , 60 , 65 , 67 , 72 ], four in South America [ 59 , 62 , 63 , 68 ], three in Asia [ 50 , 66 , 71 ], two in Australia [ 22 , 55 ] and one in Africa [ 73 ]. Most studies ( n = 23) used a cross-sectional design.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies ( n = 23) used a cross-sectional design. Studies ranged in size from a small cross-sectional study of 175 community-dwelling individuals in Albania [ 53 ] to a large population-based cohort study of 14.32 million community-dwelling Medicare beneficiaries in the USA [ 65 ]. Twenty-four studies [ 22 , 46 52 , 55 , 57 61 , 64 , 65 , 67 , 70 76 ] reported sex for 16,026,598 community-dwelling individuals aged ≥ 65 years, of whom 8,851,384 (55.2%) were female.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations